Biomaterials in orthopaedics: the past and future with immune modulation - Gun-Il Im (Biomaterials Research, 2020)
Abstracts Orthopaedics owes its current status of advanced care to the development of biomaterial science more than any other clinical medical specialty. The purpose of this brief review is to introduce the history and present status of biomaterials in orthopaedic field and cast a perspective on the future use of biomaterials to treat musculoskeletal disorders with particular emphasis on immune modulation. While the biomaterials in orthopaedics started from inert materials to replace the function and structure of hard tissue such as bone and cartilage, regenerative medicine will play a greater role in preventing the traumatic loss of tissues, as well as in the earlier stages of diseases. The understanding and modulation of immune response to biomaterials will further lead to the better incorporation of implants into host tissue or the near-perfect regeneration of host tissue.